Developing blended argumentative inquiry learning model to enhance digital literacy and critical thinking of biology students - Anwar, Muhamad Khoirul; Suratno, Suratno; Kusumaningtyas, Zulmi; Nabila, Zahra (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2026)
Digital literacy and critical thinking are essential competencies for biology students in the digital era. However, students often face challenges in evaluating digital information and constructing evidence-based arguments. This study aimed to develop a Blended Argumentative Inquiry Learning (BAIL) model and evaluate its effectiveness in improving digital literacy and critical thinking skills. The model was developed using the ADDIE model, which consisted of five stages: analysis, design, development, implementation, and evaluation. Participants were 62 undergraduate students of the Biology Education Study Program at Jember University. Data were collected through expert validation questionnaires, observation sheets, digital literacy questionnaires, and critical thinking tests. The validity and feasibility of the model were determined through expert evaluation, while effectiveness was analyzed using N-Gain scores and independent-samples t-tests. The results showed that the BAIL model was valid with expert validation score of 86% and feasible for implementation. The model effectively improved digital literacy, with the experimental group achieving a higher N-Gain score (0.41) than the control group (0.24). Critical thinking skills were also improved significantly (p = 0.025). These findings indicated that the BAIL model was an effective learning model for enhancing digital literacy and critical thinking for undergraduate biology student implemented through structured blended inquiry-based and argumentation-oriented learning activities.